2022
DOI: 10.3390/ijms23105388
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Candidate restorer-of-fertility Gene Rf3 Encoding a Pentatricopeptide Repeat Protein for the Cytoplasmic Male Sterility in Soybean

Abstract: The cytoplasmic male sterility/restorer-of-fertility (CMS/Rf) system plays a vital role in high-efficiency hybrid seed production in crops, including soybean (Glycine max (L.) Merr.). The markers linked to fertility restoration and the restorer-of-fertility (Rf) genes are essential because they can facilitate the breeding of new CMS lines and production of commercial hybrid soybean seeds. To date, several soybean Rf genes have been mapped to various genetic loci in diverse genetic populations. However, the map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…These results are consistent with previous reports and suggest that this amino acid residue encoded by S1596 is located within the core of the four-helix bundle, a region that is critical for stabilizing dimer conformation and influencing interaction partner selection [18]. Functional CAPS markers are especially helpful for marker-assisted selection, and they are widely used in the breeding of various crops and the rapid selection of novel restorer lines [42,43]. With the S1596 variations, we successfully developed a CAPS molecular marker within Rf4.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous reports and suggest that this amino acid residue encoded by S1596 is located within the core of the four-helix bundle, a region that is critical for stabilizing dimer conformation and influencing interaction partner selection [18]. Functional CAPS markers are especially helpful for marker-assisted selection, and they are widely used in the breeding of various crops and the rapid selection of novel restorer lines [42,43]. With the S1596 variations, we successfully developed a CAPS molecular marker within Rf4.…”
Section: Discussionsupporting
confidence: 92%
“…16, Glyma.16G161900 ; Rf3 , Chr. 9, Glyma.09G171200 (Sun et al, 1994a ), (Sun et al, 1994b ), (Sun, et al 2001 ), (Zhang, et al 2018a ), (Zhang, et al 2021 ), (Zhang, et al 2018c ), (Wang, et al 2010 ), (Yan, et al 2019 ), (Lin, et al 2014 ), (Guo, et al 2022 ), (Sun, et al 2022 ), (Yang, et al 2023 ) CMS-ZD ZD8319 (Zhongdou 19), Zhongyou 89B M, ZA, W931A, FuCMS5A, SXCMS1A, SXCMS5A, JLCMSZ9A Rf , Chr. 16, between BARCSOYSSR_16_1064 and BARCSOYSSR_16_1082; Rf-m , Chr.…”
Section: Cms System and Hybrid Breeding In Soybeanmentioning
confidence: 99%
“…To narrow down the candidate region for Rf1 gene for CMS-RN, Guo et al ( 2022 ) constructed an F 2 population by crossing JLCMS204A with JLR230 (restorer line), and the gene was located between the marker dCAPS-1 and BARCSOYSSR_16_1076., A recent study identified Glyma.16G161900 as the candidate gene of Rf1 (Yang, et al 2023 ). In addition, Glyma.09G171200 , encoding a pentatricopeptide repeat (PRR) protein, was confirmed as the candidate gene of another Rf3 gene for CMS-RN (Sun, et al 2022 ). In addition, the Rf gene of CMS-ZD type was located to the marker BARCSOYSSR_16_1064 and BARCSOYSSR_16_1082 on Chr.…”
Section: Cms System and Hybrid Breeding In Soybeanmentioning
confidence: 99%
“…Peng et al (1994) proposed that ZD8319, also known as Zhongdou 19 (Sun, et al 2003), processes CMS features, hereafter the relevant CMS derivative lines were distributed CMS-ZD type, which composed of Zhongyou89B, M, ZA, W931A, W933A, W936A, W945A, W948A and FuCMS1A-FuCMS3A (Zhang, et al 1999a;Sun, et al 2003). In addition, Zhao et al (1998) con rmed that a Glycine max named XXT contained cytoplasmic male sterile gene, so this kind of CMS was allocated as CMS-XX (Sun, et al 2003). However, no further study, such as cytological and function analysis, has been performed for this CMS type.…”
Section: Cms System and Hybrid Breeding In Soybeanmentioning
confidence: 99%
“…To further narrow the candidate region for Rf1 gene for CMS-RN, Guo et al ( 2022) constructed a F 2 population by crossing JLCMS204A with JLR230 (restorer line), and linked the gene between the marker dCAPS-1 and BARCSOYSSR_16_1076. In addition, Glyma.09G171200, encoding a member a pentatricopeptide repeat (PRR) protein, was con rmed as the candidate gene of another Rf3 gene for CMS-RN (Sun, et al 2022). In addition, the Rf gene of CMS-ZD type was linked to the marker BARCSOYSSR_16_1064 and BARCSOYSSR_16_1082 on Chr.…”
Section: Cms System and Hybrid Breeding In Soybeanmentioning
confidence: 99%